2011
DOI: 10.1111/j.1365-2141.2011.08635.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐centre study of therapeutic efficacy and safety of platelet components treated with amotosalen and ultraviolet A pathogen inactivation stored for 6 or 7 d prior to transfusion

Abstract: Summary Bacteria in platelet components (PC) may result in transfusion‐related sepsis (TRS). Pathogen inactivation of PC with amotosalen (A‐PC) can abrogate the risk of TRS and hence facilitate storage to 7 d. A randomized, controlled, double‐blinded trial to evaluate the efficacy and safety of A‐PC stored for 6–7 d was conducted. Patients were randomized to receive one transfusion of conventional PC (C‐PC) or A‐PC stored for 6–7 d. The primary endpoint was the 1 h corrected count increment (CCI) with an accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
245
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(257 citation statements)
references
References 32 publications
7
245
1
4
Order By: Relevance
“…Interpatient variability was further complicated by the variability of the response to transfusions in a single patient; interpretation of a study becomes more complex when randomization occurs at the patient level and not at the transfusion level. Lozano et al limited their assessment to one transfusion in order to reduce this effect [76]. It is also noteworthy that only the Janetzko study [74] formally defined the incidence of bacterial contamination as a secondary outcome, although the frequency of this complication was at an order of magnitude beyond the predictive power of these studies.…”
Section: Clinical Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Interpatient variability was further complicated by the variability of the response to transfusions in a single patient; interpretation of a study becomes more complex when randomization occurs at the patient level and not at the transfusion level. Lozano et al limited their assessment to one transfusion in order to reduce this effect [76]. It is also noteworthy that only the Janetzko study [74] formally defined the incidence of bacterial contamination as a secondary outcome, although the frequency of this complication was at an order of magnitude beyond the predictive power of these studies.…”
Section: Clinical Studiesmentioning
confidence: 98%
“…The results of six phase III randomized controlled trials (RCTs) with INTERCEPT-treated PCs have been published since 2003, as well as one with MIRASOL-treated PCs [74][75][76][77][78][79]. All of the studies had at least two study arms in which one group of patients received PI PCs, while the other received standard PCs.…”
Section: Clinical Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Hemovigilance data demonstrate a low rate of adverse events with PR platelets, 12 and some studies fail to demonstrate increased bleeding or worse clinical outcomes for patients treated with PR platelets. 13,14 However, studies have shown an association between PR platelets and a reduction in 1-and 24-hour corrected count increments, increase in platelet refractoriness, decrease in time to next transfusion, and increase in platelet use. [15][16][17] The most recent study demonstrated a 50% increase in platelets transfused and a 25% increase in red blood cells transfused in patients receiving INTERCEPT vs control platelets.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Treatment often includes prednisone, infusions of intravenous immunoglobulin, and platelet transfusion [7]. Platelet transfusion, however, can lead to antibody responses in recipients, and as a result, there has been considerable research directed at the development of pathogeninactivated platelet products to reduce the risks of these reactions [8][9][10][11][12][13]. This article is concerned with methodological challenges arising in the design and analysis of randomized trials directed at comparing the effectiveness of standard and pathogen inactivated platelets.…”
Section: Platelet Transfusion Trials In Thrombocytopeniamentioning
confidence: 99%